PHRASES AND THEIR FEATURES IN ENGLISH - Tuychieva Manzura Xodjimuradovna (Journals Park Publishing, 2024)
This article focuses on the importance of phrases in linguistics, highlighting their central role as fundamental components of sentences. It aims to demonstrate the characteristics and derivational aspects of phrases, as well as discuss different types of phrases and their variations. The research analyzes basic phrases by examining their origins. Specifically, it investigates how two independent words are connected and derived to form phrases. The outcomes of this study are presented with appropriate justifications based on the findings. Overall, this article provides insights into the structure and evolution of phrases within linguistic frameworks, emphasizing their significance in language and communication.
Keywords: phrase, derivation, types of phrase, noun phrase, adjective phrase, prepositional phrase, sentence.